Student Learning Innovations Through the Digitization System during the Covid-19 Pandemic - Muh. Nasrullah; Muhammad Luthfi Siraj (Universitas Negeri Makassar, 2022)
This study was intended to determine student learning models through the digitalization system during the Covid-19 pandemic at SMA Negeri 1 Barru Regency. This research is a descriptive qualitative type with a phenomenological research approach with data sources in this study using primary and secondary data with observation and interview data collection techniques. The data analysis technique used descriptive analysis. The results of the research for the three aspects that are indicators related to digital learning innovation carried out at SMA Negeri 1 Barru whose overall results are considered to have not created good innovation, so that the learning process implemented at SMA Negeri 1 Barru has not been able to provide stability in realizing higher quality education. quality.